Roles of oestradiol receptor alpha and beta against hypertension and brain mitochondrial dysfunction under intermittent hypoxia in female rats. (30th January 2019) - Laouafa, Sofien; Roussel, Damien; Marcouiller, François; Soliz, Jorge; Gozal, David; Bairam, Aida; Joseph, Vincent
Abstract: Aim: Chronic intermittent hypoxia (CIH) induces systemic (hypertension) and central alterations (mitochondrial dysfunction underlying cognitive deficits). We hypothesized that agonists of oestradiol receptors (ER) α and β prevent CIH‐induced hypertension and brain mitochondrial dysfunction. Methods: Ovariectomized female rats were implanted with osmotic pumps delivering vehicle (Veh), the ERα agonist propylpyraoletriol (PPT — 30 μg/kg/day) or the ERβ agonist diarylpropionitril (DPN — 100 μg/kg/day). Animals were exposed to CIH (21%‐10% FI O2 — 10 cycles/hour – 8 hours/day – 7 days) or normoxia. Arterial blood pressure was measured after CIH or normoxia exposures. Mitochondrial respiration and H2 O2 production were measured in brain cortex with high‐resolution respirometry, as well as activity of complex I and IV of the electron transport chain, citrate synthase, pyruvate, and lactate dehydrogenase (PDH and LDH). Results: Propylpyraoletriol but not DPN prevented the rise of arterial pressure induced by CIH. CIH exposures decreased O2 consumption, complex I activity, and increased H2 O2 production. CIH had no effect on citrate synthase activity, but decreased PDH activity and increased LDH activity indicating higher anaerobic glycolysis. Propylpyraoletriol and DPN treatments prevented all these alterations. Conclusions: We conclude that in OVX female rats, the ERα agonist prevents from CIH‐induced hypertension while both ERα and ERβ agonists prevent the brain mitochondrial dysfunction and metabolic switch induced by CIH. These findings may have implications for menopausal women suffering of sleep apnoea regarding hormonal therapy.